RNA Binding Proteins and Regulation of mRNA Translation in Erythropoiesis - Moore, Kat S.; von Lindern, Marieke (Frontiers in Physiology, 2018)
Control of gene expression in erythropoiesis has to respond to signals that may emerge from intracellular processes or environmental factors. Control of mRNA translation allows for relatively rapid modulation of protein synthesis from the existing transcriptome. For instance, the protein synthesis rate needs to be reduced when reactive oxygen species or unfolded proteins accumulate in the cells, but also when iron supply is low or when growth factors are lacking in the environment. In addition, regulation of mRNA translation can be important as an additional layer of control on top of gene transcription, in which RNA binding proteins (RBPs) can modify translation of a set of transcripts to the cell’s actual protein requirement. The 5′ and 3′ untranslated regions of mRNA (5′UTR, 3′UTR) contain binding sites for general and sequence specific translation factors. They also contain secondary structures that may hamper scanning of the 5′UTR by translation complexes or may help to recruit translation factors. In addition, the term 5′UTR is not fully correct because many transcripts contain small open reading frames in their 5′UTR that are translated and contribute to regulation of mRNA translation. It is becoming increasingly clear that the transcriptome only partly predicts the proteome. The aim of this review is (i) to summarize how the availability of general translation initiation factors can selectively regulate transcripts because the 5′UTR contains secondary structures or short translated sequences, (ii) to discuss mechanisms that control the length of the mRNA poly(A) tail in relation to mRNA translation, and (iii) to give examples of sequence specific RBPs and their targets. We focused on transcripts and RBPs required for erythropoiesis. Whereas differentiation of erythroblasts to erythrocytes is orchestrated by erythroid transcription factors, the production of erythrocytes needs to respond to the availability of growth factors and nutrients, particularly the availability of iron.